PERSEPSI WISATAWAN NUSANTARA TERHADAP KEBERSIHAN PASAR SENI SUKAWATI KABUPATEN GIANYAR BALI - Ni Wayan Nurtini; Ida Ayu Suryasih (JURNAL DESTINASI PARIWISATA, 2013)
ABSTRACT The background of this research is the management of the Sukawati Art Market hygiene should be improved to help increase the number of visits. Sukawati Art Market is a traditional market which is quite famous in Bali, where the market sells a variety of shirts and pants Balinese located in the village of Sukawati, Gianyar regency, 18 km from the Denpasar and can be reached by a two-wheeled vehicle or four wheel. The purpose of this study is to know about domestic tourist perceptions towards hygiene Gianyar Sukawati Art Market. Perception is referred to in this research is the opinion of the travelers Sukawati Art Market covering several areas including market areas, parking lots, acreage and the last merchants toilet area. Type of data used is the qualitative data and quantitative data. Sources of data used in this study is primary data and secondary data. Methods of data collection through in-depth interviews, observations, questionnaires and documentation. Analysis of the data used is descriptive qualitative. The results showed that the Sukawati art market is very clean. Head of the Sukawati Art Market has provided 10 people with 3 staff hygiene market division is the first part of the hours of 6 am to finish 10 employees, the second part of the hours of 11 noon to 1 pm with 3 employees, and the last third part 4pm to finish with 7 employees. Employees - employees are always working on his own routine - each, so the Sukawati Art Market always looks clean.